2015
DOI: 10.1681/asn.2014040350
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Endothelial Growth Factor-A165b Is Protective and Restores Endothelial Glycocalyx in Diabetic Nephropathy

Abstract: Diabetic nephropathy is the leading cause of ESRD in high-income countries and a growing problem across the world. Vascular endothelial growth factor-A (VEGF-A) is thought to be a critical mediator of vascular dysfunction in diabetic nephropathy, yet VEGF-A knockout and overexpression of angiogenic VEGF-A isoforms each worsen diabetic nephropathy. We examined the vasculoprotective effects of the VEGF-A isoform VEGF-A 165 b in diabetic nephropathy. Renal expression of VEGF-A 165 b mRNA was upregulated in diabet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
166
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 117 publications
(177 citation statements)
references
References 58 publications
(67 reference statements)
8
166
0
2
Order By: Relevance
“…This twice weekly i.p. dosing regime has proven successful in the amelioration of diabetic nephropathy [21], traumatic nerve injury [16] and in vivo tumour models [22]. .…”
Section: Experimental Animals and Proceduresmentioning
confidence: 99%
“…This twice weekly i.p. dosing regime has proven successful in the amelioration of diabetic nephropathy [21], traumatic nerve injury [16] and in vivo tumour models [22]. .…”
Section: Experimental Animals and Proceduresmentioning
confidence: 99%
“…12,[24][25][26] Importantly, postmitotic podocytes exhibit high levels of basal autophagy as a key regulator of podocyte and glomerular maintenance. 13 Additionally, a strong body of evidence supports the role for maintenance of endothelial function in diabetes to limit DN progression involving homeostasis of multiple systems 7,[27][28][29][30] such as NOS3/eNOS (nitric oxide synthase 3 [endothelial cell]) activity, 31 glycocalyx production, 32,33 EDN/endothelin actions [34][35][36][37][38] and balanced VEGF (vascular endothelial growth factor) 33,39,40 and ANGPT/angiopoietin systems. 41 Endothelial cells may also use autophagy as a coping mechanism to metabolic stress.…”
Section: Introductionmentioning
confidence: 99%
“…22 VEGFA isoform VEGF-A165b is proved to have the vasculoprotective effects against DN. 23 Besides, sub-network 2 with VEGFA as the centre node was screened in our paper. Function analysis showed that sub-network 2 was closely related with cell proliferation regulation related biological process.…”
Section: Discussionmentioning
confidence: 99%